Influência da estrutura no comportamento hidromecânico de um solo tropical residual de gnaisse do complexo Belo Horizonte - Domingos José de Paula Neto (2019)
The objective of this work is to study the influence of the original structure of gnaisse’s tropical residual soil native of the Complexo Belo Horizonte’s geological formation, collected in a test area known as Block 10 (Q10), in the Pampulha campus of the Federal University of Minas Gerais (UFMG). Residual soils may have cementations developed through the bond between soil particles. Those bonds might be formed during physical-chemical-biological weathering evolution of the matrix of the rock acting along its profile. This thesis seeks to contribute to the understanding of the original soil structure role on permeability, compressibility, shear strength, and stress-strain behavior on both saturated and non-saturated conditions by evaluating its physical, hydraulics and mechanics properties. That being said, the microstructural characteristics, as well as the mineralogical composition and the lateralization (MCT’s classification) of this soil were evaluated through laboratorial tests that include tests such as: determining the physical parameters (specific grain’s gravity, size distribution, and Atterberg limits), porosimeter’s test by mercury intrusion, microscopical electronic analysis, and X-Ray dispersion. In addition, permeability on variable head was tested in one sample molded from an undisturbed block and others were reconstructed with the same characteristics. Furthermore, unidimensional consolidation saturated and unsaturated tests were developed in which the permeability variable head was determined in each load stage for the saturated condition. In conclusion, shear strength assessments were made on undisturbed and reconstructed samples on saturated condition and on hygroscope moisture content. According to Delcourt (2018), the soil structure influence can be defined when behavior differences between the undisturbed sample and the reconstructed ones are analyzed within the same porosity and saturated conditions under the effect of the same load condition. Therefore, the structural influence on hydromechanics behavior of this soil was verified by the comparison between the results obtained through laboratorial tests on undisturbed and reconstructed samples with the same physical properties.